Desert Environment Effect on the Deterioration of Ancient Building Materials in Archaeological Buildings (El- Bagawat Tombs, El - Kharga Oasis as an Example) - Shaimaa Sayed Mohamed El-Sayed; Rabea Radi Abdel Kader; Ahmed Abo-El Yamin (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Environmental changes have severe effect on the deterioration of archaeological buildings, desert environment distinguishes with the climatic changes daily and seasonally , which affect badly on the ancient building materials, air temperature variation, relative humidity and wind are the main factors that cause the materials degradation. This research aims to shed the light on desert environment's effect on ancient building materials at El - Bagawat tombs in El- Kharga oasis – Egypt, these tombs, return to early Coptic era, building materials samples were taken mainly mud bricks and mortars , examined and analyzed by scanning electron microscope (SEM) , EDAX unit attached to SEM and polarizing microscope to study the desert's effect , environmental measures were mentioned also like air temperature degrees , relative humidity percentages and wind's direction and speed. El-Kharga oasis is characterized by climate changes throughout the year, these changes reflect on the degradation of building materials in El-Bagawat tombs like mud bricks and mortars.